The American Business Judgment Rule and Swedish Law - A Comparative Analysis of the American Business Judgment Rule and Its Eventual Counterpart in Swedish Law - Rosberg,Erik (2019)
The purpose of this thesis is to examine whether Swedish directors and CEOs can expect the Swedish courts to review business decisions in a similar way to how the American courts review business decisions. This examination enables a comparative analysis of whether something similar to the American business judgment rule exists in Swedish law, which some Swedish legal scholars claim. The American courts are prohibited to review business decisions as long as the business judgment rule presumption is not rebutted. The American courts simply presume that in making a business decision, the directors of a corporation acted on an informed basis, in good faith, and in the honest belief that the action was taken in the best interests of the company. There are conflicting statements about how the Swedish courts review business decisions according to the rules about liabilities of directors and CEOs in Swedish law. Lindskog, the Former Chief Justice of the Supreme Court of Sweden, states that the Supreme Court of Sweden has started to use the method liability when they accomplish the negligence assessment. According to the method liability, it is the considerations behind the decision that are reviewed and not the decision itself. Some legal scholars state that the fact that the business purpose in Chapter 3, Section 3 of the Swedish Companies Act is formulated in a vague way gives the directors and CEO a broad discretion to fulfill the business purpose and to make business decisions within the ordinary course of business. Other legal scholars state that Swedish courts do not review whether a business decision is unwise and that risky business decisions usually do not make the directors and CEO liable, at least as long as the business decisions are within the ordinary course of business. However, a Swedish court case demonstrates that there are no restrictions regarding what kind of business decisions the Swedish courts can review and that they are unhindered to make an assessment of business decisions. There does not seem to be a similarity between how American courts review business decisions according to the American business judgment rule and how Swedish courts review business decisions according to the rules about liabilities of directors and CEOs in Swedish law. There are tendencies that indicate that something similar to the American business judgment rule exists in Swedish law but it is unclear what the applicable prerequisites are in Swedish law. However, there are clear prerequisites in American law that clarify under what circumstances the American courts are allowed to review business decisions. The American business judgment rule presumption is a powerful shield against liability for the American directors. There is no such presumption in Swedish law that needs to be rebutted in order for the courts to review business decisions. This means that Swedish directors and CEOs do not seem to be able to make risky business decisions without fear of becoming liable. Therefore, it is misleading to state that there is something similar to the American business judgment rule in Swedish law.
Keywords: The Business Judgment Rule; Business Judgment Rule; BJR; Director; Board of Directors; Officer; Chief Executive Officer; CEO; Directors’ Duties; Liabilities; Method Liability; Shareholder; Business Law; Corporate Law; Corporation Law; Comparative Law; American Law; U.S. Law; Swedish Law; United States; United States of America; Sweden; Model Business Corporation Act; MBCA; Delaware General Corporation Law; DGCL; Delaware; Swedish Companies Act; styrelse; verkställande direktör; VD; styrelseansvar; skadestånd; skadeståndsskyldighet; metodansvar; aktieägare; associationsrätt; aktiebolagsrätt; bolagsrätt; förmögenhetsrätt; komparativ rätt; amerikansk rätt; svensk rätt; USA; Sverige; aktiebolagslag; ABL